A study of S doped ZnSb. (15th November 2017) - Song, X.; Finstad, T.G.
Abstract: We report on S-doping of ZnSb for S concentrations ranging from 0.02 at% to 2.5 at%. There are no previous reports on S-doping. ZnSb is a thermoelectric material with some advantages for the temperature range 400 K–600 K. The solid solubility of S in ZnSb was estimated to be lower than 0.1% from observations of precipitates by scanning microscopy. Hall and Seebeck measurements were performed as a function of temperature from 6 K to 623 K. The temperature dependence of the electrical properties suggests that S introduces neutral scattering centers for holes in the p-type material. An increase in hole concentration by S is argued by defect reactions involving Zn vacancies.